Ecomuseo: una propuesta metodológica - Alfredo Miranda-Calderón; Elizabeth Alpízar-Barrantes (Universidad Nacional, Costa Rica, 2011)
This article is part of a project intended to facilitate pedagogical meditation among all of us who teach and learn in one room/one teacher schools. It is addressed to all teachers who must share classrooms comprised by students of different ages, interests and levels of competence, a situation that is brought about by the location an characteristics of their schools. Also, the real needs these teachers have, as well as the opinions of students attending one-teacher schools are also taken into account. Each one of the activities conforming this proposal is designed to promote learning in a natural context, for they involve all the elements available at these schools. The experiences developed include observation, research and skill development. All the activities suggested here serve as a means for teachers who teach different grades simultaneously so they can transmit to their students knowledge about, understanding and valuation of their natural surroundings gradually and in an holistic way.